Sequence Stratigraphy of the Lower Miocene Moghra Formation in the Qattara Depression, North Western Desert, Egypt - Hassan, Safiya M. (SpringerBriefs in Earth Sciences,, 2013)
The Qattara Depression is part of the Northwestern Desert in Egypt and is home to the second lowest point in Africa at -133 meters below sea level. Therefore, before any projects can be carried out in this area, we must first understand the geology of the land. The present study deals with the high-resolution sequence stratigraphic analysis of the Lower Miocene Moghra Formation outcrops in the Qattara Depression Region. The literature on the sedimentology and sequence stratigraphy of the Moghra Formation has been sparse to date, despite some excellent work over the years by academic and petroleum workers. Moreover, the area studied is within what was once a front-line of World War II, where mine fields and war relics are scattered and cover wide reaches. This has resulted in limited geologic mapping in the past. Thus, great attention is paid in this study to establishing a robust sedimentology and high-resolution sequence stratigraphic framework for the Lower Miocene Moghra Formation. Included are works based on outcrops and, most importantly, new sedimentological and chronostratigraphic information not previously available.